1997
DOI: 10.2105/ajph.87.1.71
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and cancer incidence among sawmill workers exposed to chlorophenate wood preservatives.

Abstract: OBJECTIVES: This study examined the association between exposure to chlorophenates and the risk of soft tissue sarcoma; non-Hodgkin's lymphoma; Hodgkin's disease; and cancers of the lung, nose, and nasopharynx. METHODS: A retrospective cohort study was conducted of 26487 workers employed for at least 1 year between 1950 and 1985 in 11 chlorophenate-using and 3 non-using sawmills in British Columbia, Canada. Exposures by job were ascertained with interviews of senior employees. RESULTS: Probabilistic record lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 29 publications
(3 reference statements)
0
52
0
Order By: Relevance
“…Case reports and case-control studies of hematopoietic cancers published in the 1980s and 1990s indicated the risk of non-Hodgkin lymphoma, soft-tissue sarcoma and multiple myeloma in relation to pentachlorophenol exposure for (Greene et al, 1978;Bishop et al, 1981;Pearce et al, 1986;Smith et al, 1992;Hardell et al, 1994;Hardell et al, 1995;Kogevinas et al, 1995). In the 1990s and 2000s, four cohort studies reported the results between cancer risk and PCP exposure, and most of them reported weak or no risk of exposure to PCP, the authors infer the non-significant results might due to the less study population and healthy worker effects (Hertzman et al, 1997;Demers et al, 2006;Ramlow et al, 1996;Ruder et al, 2011). After it has been forbidden to use in many countries, a worldwide research suggests that in indoor air, bodies of water, and freshwater sediments around the world, PCP levels has declined over time (Zheng et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Case reports and case-control studies of hematopoietic cancers published in the 1980s and 1990s indicated the risk of non-Hodgkin lymphoma, soft-tissue sarcoma and multiple myeloma in relation to pentachlorophenol exposure for (Greene et al, 1978;Bishop et al, 1981;Pearce et al, 1986;Smith et al, 1992;Hardell et al, 1994;Hardell et al, 1995;Kogevinas et al, 1995). In the 1990s and 2000s, four cohort studies reported the results between cancer risk and PCP exposure, and most of them reported weak or no risk of exposure to PCP, the authors infer the non-significant results might due to the less study population and healthy worker effects (Hertzman et al, 1997;Demers et al, 2006;Ramlow et al, 1996;Ruder et al, 2011). After it has been forbidden to use in many countries, a worldwide research suggests that in indoor air, bodies of water, and freshwater sediments around the world, PCP levels has declined over time (Zheng et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Over the past decade we have gathered a cohort of approximately 28 000 British Columbia sawmill workers who worked in 1 of 14 sawmills between 1950 and 1998 (20). As part of a study on technological change a subcohort of 9806 workers was identified.…”
Section: Methodsmentioning
confidence: 99%
“…The study population was originally enumerated for a study of fungicide exposure and cancer and later expanded to include other health outcomes and exposures, including noise, stress and wood dust (Hertzman et al 1997;Teschke et al 1998). The study cohort consisted of 27,499 male sawmill workers employed one or more years between 1950 and 1995 in 14 sawmills in British Columbia (BC), Canada.…”
Section: Study Populationmentioning
confidence: 99%